2023
DOI: 10.1111/1744-7917.13174
|View full text |Cite
|
Sign up to set email alerts
|

eIF3 subunit M regulates blood meal digestion in Rhodnius prolixus affecting ecdysis, reproduction, and survival

Abstract: In triatomines, blood‐feeding triggers many physiological processes including post embryonic development and reproduction. Different feeding habits, such as hematophagy, can shape gene functions to meet the challenges of each type of diet. The gut of blood‐sucking insects faces particular challenges after feeding due to the quantity and the quality of the food ingested. A comparison of transcriptomic and proteomic data indicates that post transcriptional regulation of gene expression is crucial in the triatomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Regardless, it is not possible to formally exclude the possibility that the translation initiation function might be performed by eIF3f2. A series of recent studies have demonstrated that some of the fly eIF3 subunits, for instance eIF3d, eIF3m, and eIF3j, are involved in regulating tissue/organ development, stress response, and so on (Ameijeiras et al, 2023 ; Ramat et al, 2020 ; Song et al, 2022 ; Szostak et al, 2018 ). All these functions are fulfilled through a translational control-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, it is not possible to formally exclude the possibility that the translation initiation function might be performed by eIF3f2. A series of recent studies have demonstrated that some of the fly eIF3 subunits, for instance eIF3d, eIF3m, and eIF3j, are involved in regulating tissue/organ development, stress response, and so on (Ameijeiras et al, 2023 ; Ramat et al, 2020 ; Song et al, 2022 ; Szostak et al, 2018 ). All these functions are fulfilled through a translational control-dependent manner.…”
Section: Discussionmentioning
confidence: 99%